2018
DOI: 10.1021/acs.jproteome.8b00001
|View full text |Cite
|
Sign up to set email alerts
|

PPARα Is Necessary for Radiation-Induced Activation of Noncanonical TGFβ Signaling in the Heart

Abstract: High-dose ionizing radiation is known to induce adverse effects such as inflammation and fibrosis in the heart. Transcriptional regulators PPARα and TGFβ are known to be involved in this radiation response. PPARα, an anti-inflammatory transcription factor controlling cardiac energy metabolism, is inactivated by irradiation. The pro-inflammatory and pro-fibrotic TGFβ is activated by irradiation via SMAD-dependent and SMAD-independent pathways. The goal of this study was to investigate how altering the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 67 publications
5
17
0
Order By: Relevance
“…The functional analysis of deregulated proteins analysis predicted inactivation of PPAR alpha, a key transcriptional regulator of fatty acid metabolism, in irradiated samples. The impairment of the PPAR alpha pathway and inhibition of lipid metabolism enzymes have been repeatedly reported in radiation-induced cardiac damage [5,37,41,42]. We have shown previously the upregulation of the inactive (phosphorylated) form of PPAR alpha in cardiac samples of Mayak workers [5].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The functional analysis of deregulated proteins analysis predicted inactivation of PPAR alpha, a key transcriptional regulator of fatty acid metabolism, in irradiated samples. The impairment of the PPAR alpha pathway and inhibition of lipid metabolism enzymes have been repeatedly reported in radiation-induced cardiac damage [5,37,41,42]. We have shown previously the upregulation of the inactive (phosphorylated) form of PPAR alpha in cardiac samples of Mayak workers [5].…”
Section: Discussionsupporting
confidence: 53%
“…The morphology analysis also indicated large foci of fibrotic tissue in the irradiated samples although in comparison with the controls this did not reach statistical significance. Increased expression of proteins involved in the fibroblast to myofibroblast differentiation was shown in mice after high doses of local heart irradiation, with the activation of TGF beta playing a central role [41]. Increased concentration of TGF beta has been reported in the serum of Mayak workers exposed to external gamma rays suggesting a systemic elevation in the level of this cytokine in this cohort [45].…”
Section: Discussionmentioning
confidence: 80%
“…The classical TGF-b1/Smad signaling pathway plays an important role in tumor development and progression. Subramanian et al (2018) found that activation of TGF-b1/ Smad and non-Smad signaling pathways was detected after 8 Gy local IR of mouse hearts. found that the expression of TGF-b1 in lung tissue was increased in 15 Gy-irradiated mice following IR of the whole chest, and the levels of phosphorylated Smad2 and Smad3 were upregulated.…”
Section: Discussionmentioning
confidence: 96%
“…Typically, cardiac symptoms appear late, sometimes decades after exposure to radiation, and include increased infiltration of inflammatory cells and fibrosis of the myocardium, especially after receiving high radiation doses (5). In addition to vascular abnormalities, recent studies have emphasized cardiac fibrosis as a major causal factor for radiation-induced heart disease (6), a condition that is accompanied by an accumulation of fibroblasts and fibroblast-to-myofibroblast transition (FMT) (7).…”
Section: Introductionmentioning
confidence: 99%